Perkembangan Sektor Keuangan di Indonesia: Sebuah Studi Literatur - Ivana Dea Amelia; Syamsul Hidayat (Asosiasi Riset Ilmu Manajemen dan Bisnis Indonesia, 2025)
This study aims to analyze and understand the development of the financial sector in Indonesia through a literature review covering four main aspects: banking, financial digitalization, fiscal reforms, and financial literacy, as well as their impact on economic growth and public welfare. This literature review summarizes various findings and theories regarding the dynamics of the financial sector in efforts to maintain economic stability in Indonesia. The research findings indicate that the development of the banking sector plays a significant role in driving economic growth, particularly in expanding access to financing and improving the ease of fund distribution. In addition, digitalization strengthens the growth of financial technology by expanding access to financial services. Ongoing development of technology policies aims to address challenges in financial digitalization to make it more effective and secure. Furthermore, well-targeted fiscal reforms aim to improve productivity and economic stability. Meanwhile, the public also needs to cultivate wiser financial behavior to maximize the utilization of financial services as part of enhancing financial literacy. In conclusion, the positive impact of the advancement of the financial sector benefits economic growth and public welfare in Indonesia. This study emphasizes the importance of fostering collaboration between government policies, digital innovation, strengthening financial institutions, and helping the public enhance their capabilities to create a more inclusive and sustainable financial ecosystem.